Riset Penggunaan Pemanas Air Tenaga Surya di Perhotelan Indonesia - Sebuah Kajian Literatur - Samar Tan; Richard A M Napitupulu (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2019)
Hospitality is a relatively large energy user in the tourism sector. The application of renewable energy in this field will certainly save energy and contribute to reduce the effect of global warming. An interesting application to study is the use of solar energy for preparing hot water in hotel. This study is a literature study that explored research articles on solar water heater, especially used in hospitality, that have been published. Studies on solar energy have always increased over the past five years, 66.2% of which were in the field of solar thermal energy, where 11.2% of solar thermal energy researches were related to the use of solar energy for the process of heating water. For the research originating from Indonesia, the figures are 48.7% and 6.6% respectively. There is no research on the use of solar water heater in Indonesia. Research on tourism in Indonesia itself tends to decline. A simple example of simulation about solar water heating system using TRNSYS 18 simulation program was presented to motivate researchers in this field.